Learning from Case Studies in the Career Development of a Clinical Psychologist - WATANABE, Shingo (Journal of Japanese Society of Geriatric & Gerontological Behavioral Sciences, 2024)
I have been a clinical psychologist for 16 years and have accumulated clinical experience spanning diverse settings, including prisons, correctional facilities, general hospitals with no psychiatry departments, and orthopedic hospitals. In these roles, I have encountered moments of helplessness and personal challenges. However, upon reflection, I realize these experiences have provided valuable professional and personal insights and learning opportunities. In this article, I first outline the professional field and role of clinical psychologists and then explore critical case studies that have shaped my career development. Lastly, I discuss how professional identity evolves alongside career growth and reflect on the broader implications for the career development of clinical psychologists.